180k views
0 votes
The first step in the process for factoring the trinomial x^2-3x-40 is to

2 Answers

1 vote

Answer:

= (x - 8)(x + 5)

If it is an equation which just means it is equal to zero e.g. x^2 - 3x - 40 = 0

then we would continue and write our x values!

So assuming it was an equation here is the rest of the working:

x - 8 = 0 x + 5 = 0

x = 8 x = -5

x = 8, x = -5

Hope this helped!

Explanation:

User Alex Kamaev
by
4.5k points
6 votes

(x-8)(x+5)

First thing you do is put the X's into the parentheticals because it is x^2 meaning there are 2 factors with x's. Then, you wonder what factors of -40 could add to get -3. In this case, they are -8 and 5. -8 times 5 is -40 and -8 +5 is -3. Then, you just add -8 and 5 beside the x's in the parentheticals.

User Nitin Labhishetty
by
4.5k points